Bedside tests for predicting difficult airways: an abridged Cochrane diagnostic test accuracy systematic review. (6th March 2019) - Roth, D.; Pace, N. L.; Lee, A.; Hovhannisyan, K.; Warenits, A. M.; Arrich, J.; Herkner, H.
Summary: Although bedside screening tests are routinely used to identify people at high risk of having a difficult airway, their clinical utility is unclear. We estimated the diagnostic accuracy of commonly used bedside examination tests for assessing the airway in adult patients without apparent anatomical abnormalities scheduled to undergo general anaesthesia. We searched for studies that reported our pre‐specified bedside index screening tests against a reference standard, published in any language, from date of inception to 16 December 2016, in seven bibliographic databases. We included 133 studies (127 cohort type and 6 case–control) involving 844, 206 participants. Overall, their methodological quality (according to QUADAS‐2, a standard tool for assessing quality of diagnostic accuracy studies) was moderate to high. Our pre‐specified tests were: the Mallampati test (6 studies); modified Mallampati test (105 studies); Wilson risk score (6 studies); thyromental distance (52 studies); sternomental distance (18 studies); mouth opening test (34 studies); and the upper lip bite test (30 studies). Difficult facemask ventilation, difficult laryngoscopy, difficult intubation and failed intubation were the reference standards in seven, 92, 50 and two studies, respectively. Across all reference standards, we found all index tests had relatively low sensitivities, with high variability, but specificities were consistently and markedly higher than sensitivities. For difficult laryngoscopy, the sensitivity and specificity (95%CI) of the upper lip bite test were 0.67 (0.45–0.83) and 0.92 (0.86–0.95), respectively; upper lip bite test sensitivity (95%CI) was significantly higher than that for the mouth opening test (0.22, 0.13–0.33; p < 0.001). For difficult tracheal intubation, the modified Mallampati test had a significantly higher sensitivity (95%CI) at 0.51 (0.40–0.61) compared with mouth opening (0.27, 0.16–0.41; p < 0.001) and thyromental distance (0.24, 0.12–0.43; p < 0.001). Although the upper lip bite test showed the most favourable diagnostic test accuracy properties, none of the common bedside screening tests is well suited for detecting unanticipated difficult airways, as many of them are missed. Abstract : 困難気道の高リスク者をスクリーニングするためのベッドサイド検査は日常的に行われているが, その臨 床的有用性は不明である。全身麻酔が予定され, 明らかな解剖学的異常のみられない成人患者を対象とし て, 気道評価によく用いられるベッドサイド検査の診断精度を評価した。7 つの文献データベースにおいて, 収載開始日~2016 年12 月16 日を対象に, 言語を問わず, 困難気道を予測するベッドサイド検査の診 断精度に関する研究を検索した。研究133 件(コホート研究127 件, 症例対照研究6 件)(被験者844, 206例)を検討対象とした。全体において, 研究の方法の質(診断精度に関する研究の質を評価する標準ツールであるQUADAS‐2 による)は「中」~「高」であった。事前に規定したベッドサイド検査(研究件数)は, Mallampati 分類(6 件), 修正Mallampati 分類(105 件), Wilson リスクスコア(6 件), 頤‐ 甲状軟骨間距離(52 件), 頤‐ 胸骨間距離(18 件), 開口距離(34 件), upper lip bite test(30 件)であった。困難気道イベントの参照基準(研究件数)は, マスク換気困難(7 件), 喉頭展開困難(92 件), 挿管困難(50 件), 挿管失敗(2 件)であった。すべての参照基準を通じ, いずれのベッドサイド検査も感度が比較的低く, ばらつきが大きかったが, 特異度は感度よりも一貫してかつ著明に高かった。喉頭展開困難に関し, upper lip bite test の感度[95%信頼区間(CI)]は0.67(0.45~0.83), 特異度(95% CI)は0.92(0.86~0.95)であり, upper lip bite test の感度(95% CI)は開口距離[0.22(0.13~0.33), p < 0.001]よりも有意に高かった。気管挿管困難に関し, 修正Mallampati分類の感度(95% CI)は0.51(0.40~0.61)であり, 開口距離[0.27 (0.16~0.41), p < 0.001]および頤‐ 甲状軟骨間距離[0.24(0.12~0.43), p < 0.001]と比較して有意に高かった。upper lip bite test の診断検査精度が最も良好であったが, よく用いられるベッドサイド検査はいずれも予想外の困難気道の多くを見逃しており, その特定に十分適した検査法は認められない。